Peningkatan Pengetahuan Videografi sebagai Upaya Pendukung Promosi Produk UMKM - Ilmadina, Hepatika Zidny; Apriliani, Dyah; Maulana, Ahmad (Universitas Nusantara PGRI Kediri, 2023)
Current information technology has been implemented in various fields, such as education, religion, health, social, and culture. Nowadays, Smartphones and social media are a way out of communicating, digging information activities, to buying and selling transactions. The use of information technology has also proliferated, not only for companies and business actors, but almost all people use and utilize information technology. The Tegal City Government itself has created a social media-based promotional platform, namely the UMKM gallery, that can be accessed by Micro, Small and Medium Enterprises (MSME) sector actors to promote their products. However, in carrying out these promotions, they need exciting content to attract buyers. MSMEs need expertise in drafting concepts and editing images and videos as promotional breakfasts. So it is essential to make an effort to improve videography that can be used as a means of marketing the products of business people, in this case, MSME’s products. This activity was carried out with the support of the Canva application to create product promotional content. Canva is an online design program application that provides various editing tools or tools to create various graphic designs in the form of templates, features, and categories provided in it easily without the need to design it from scratch. The results of this activity are several designs made by MSME actors in promoting their products. Increased knowledge can be seen from the design results shared on their social media such as WhatsApp, Instagram, and others.